Lower Limb Loading in Step Aerobic Dance - Wu, H.-W.; Hsieh, H.-M.; Chang, Y.-W.; WANG, L.-H. (International Journal of Sports Medicine, 2012)
Participation in aerobic dance is associated with a number of lower extremity injuries, and abnormal joint loading seems to be a factor in these. However, information on joint loading is limited. The purpose of this study was to investigate the kinetics of the lower extremity in step aerobic dance and to compare the differences of high-impact and low-impact step aerobic dance in 4 aerobic movements (mambo, kick, L step and leg curl). 18 subjects were recruited for this study. High-impact aerobic dance requires a significantly greater range of motion, joint force and joint moment than low-impact step aerobic dance. The peak joint forces and moments in high-impact step aerobic dance were found to be 1.4 times higher than in low-impact step aerobic dance. Understanding the nature of joint loading may help choreographers develop dance combinations that are less injury-prone. Furthermore, increased knowledge about joint loading may be helpful in lowering the risk of injuries in aerobic dance instructors and students.
Keywords: aerobic dance; step aerobic; joint loading; kinematics; kinetics